2008
DOI: 10.1177/097226290801200404
|View full text |Cite
|
Sign up to set email alerts
|

Study of Customer Relationship Marketing Practices in Organised Retailing in Food and Grocery Sector in India: An Empirical Analysis

Abstract: The fast changing trends in lifestyles, food and eating habits ofconsumers have contributed largely to the growth and development oforganisedfood andgrocery retailformats in India. But, this sector is predominantly (99.2 percent) dominated by the traditional kirana stores, which have strong relationships with the customers for various technical andfunctional quality benefits extended to them. This posed a great challenge to the organised retailers for customer acquisition and retention ofloyal customers in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 45 publications
1
21
0
1
Order By: Relevance
“…Several previous studies revealed the existence of a positive relationship between customer satisfaction and loyalty (e.g., Hallowell, 1996;Homburg and Giering, 2001;Ming-Tien et al, 2010;Prasad and Aryasri, 2008;Wallace et al, 2004). Others authors showed the following positive effects of customer satisfaction: customer retention (Bolton and Lemon, 1999;Rust and Zahorik, 1993), repurchase intention (Bolton and Lemon, 1999;Taylor and Baker, 1994), repurchase behaviour (Anderson and Sullivan, 1993;Cronin Jr et al, 2000;Mittal and Kamakura, 2001), positive references (word-ofmouth) to potential customers (Bitner, 1990;Grönroos, 2004;Palmatier et al, 2006;Swan and Oliver, 1989).…”
Section: Customer Satisfactionmentioning
confidence: 99%
“…Several previous studies revealed the existence of a positive relationship between customer satisfaction and loyalty (e.g., Hallowell, 1996;Homburg and Giering, 2001;Ming-Tien et al, 2010;Prasad and Aryasri, 2008;Wallace et al, 2004). Others authors showed the following positive effects of customer satisfaction: customer retention (Bolton and Lemon, 1999;Rust and Zahorik, 1993), repurchase intention (Bolton and Lemon, 1999;Taylor and Baker, 1994), repurchase behaviour (Anderson and Sullivan, 1993;Cronin Jr et al, 2000;Mittal and Kamakura, 2001), positive references (word-ofmouth) to potential customers (Bitner, 1990;Grönroos, 2004;Palmatier et al, 2006;Swan and Oliver, 1989).…”
Section: Customer Satisfactionmentioning
confidence: 99%
“…Trust can also be defined as the willingness to rely on a trusted and well-meaning partner. If customers receive high-quality services and are aware that service personnel are reliable and genuine, positive word of mouth will form (Prasad and Aryasri, 2008;Monferrer-Tirado et al, 2016). Caceres and Paparoidamis (2007) argued that long-term loyalty entails commitment, where if a customer has brand commitment, three important behavioral outputs will result: repeated purchase of the brand's products, offsetting of changes caused by competition, and offsetting of negative feelings caused by dissatisfaction.…”
Section: Experiential Valuementioning
confidence: 99%
“…It has been indicated in the studies from Ai (2016), Wu H. C. et al (2018) that high trust and satisfaction arising from the process of experience are conducive to generating high customer loyalty. In longterm relationships with customers, if customers' commitment can be continuously maintained, their relationship with the firm will be enhanced, which will increase purchase frequency (Prasad and Aryasri, 2008;Arcand et al, 2017). Furthermore, Caceres and Paparoidamis (2007) argued that the development of trust and commitment is strategically important, because it creates a relationship atmosphere between the two parties and directly affects the customer's behavioral intentions (Monferrer-Tirado et al, 2016).…”
Section: Experiential Valuementioning
confidence: 99%
“…Currently, customer loyalty and satisfaction become very important for the bank, and this has been studied and discussed in a lot of research and literature. Prasad and Aryasri (2008) argued that marketing can consistently identify customer satisfaction as well as be a key to customer loyalty. In addition, customer satisfaction can provide many benefits for the company because higher level of customer satisfaction will result in greater customer loyalty (Lovelock and Wright, 2007).…”
Section: Introductionmentioning
confidence: 99%